RISIKO KREDIT PORTOFOLIO OBLIGASI DENGAN CREDIT METRICS DAN OPTIMALISASI PORTOFOLIO DENGAN METODE MEAN VARIANCE EFFICIENT PORTFOLIO (MVEP) - Nurul Fauziah; Abdul Hoyyi; Di Asih I Maruddani (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2012)
Investing is a important thing in a capital market. Bond investment must be noticed the risk especially credit risk. From the information of credit risk, investor can choose the right investment. Credit Metrics is a reduced form model to estimate the risk. Credit Metrics is centered by the corporate rating. The risk not only occur when corporate rating be default but also if the rating upgrade or downgrade. For a bond portfolio, can calculate the optimal portfolio by Mean Variance Efficient Portfolio method. Empirical study can be used for two bonds, first bond is Obligasi Adira Dinamika Multi Finance V Tahun 2011 Seri A and second one is Obligasi BFI Finance Indonesia III Tahun 2011 Seri A. First bond has 127.01640 (Billion) of credit risk and the second one bonds has 18.33472 (Billion). For a portfolio of that two bonds, they have 179.82460 (Billion). For the optimal portfolio, first bond has propotion 66.39% and 33.61% for the second bond.